Photovoltaic effect at spin resonance in quantum magnetic field - Chernyshov, N.N.; Belousov, A.V.; Alkhawaldeh, M.A.F.; Pisarenko, V.M.; Rogozin, I.V. (Радіофізика та електроніка, 2018)
The article is devoted to the investigation of the photovoltaic effect in n-InSb under optical transitions between the spin subbands of the Landau levels for the ultraquantum limit. The geometry is considered when the polarization is perpendicular, and the current is directed along the magnetic field. The effect is due to the cubic terms in the Hamiltonian that exist due to the absence of an inversion center. The dependence of the current on the magnetic field has a resonance character. Such an effect is associated with resonance in the intermediate state and interference of the second-order transition amplitudes with respect to relativistic contributions to the Hamiltonian. The aim of the work is a theoretical and experimental study of the photovoltaic effect for spin resonance.